Voice Warning to Identify Distance to Obstacles on Smart Cane for Blind People - Atmiasri, Atmiasri; Solikin, Akhmad; Zukro A., Rasyida Shabihah (Universitas Nurul Jadid, 2023)
Blind people are often hampered in their mobility, while currently available assistive technology includes manual sticks and electronic mobility devices. Currently, the development of smart canes is still being carried out in many studies. Smart cane works by detecting the distance of the cane to obstacles in front of you. From detecting this distance, the response the user gets is generally in the form of vibrations and sounds from the buzzer. The sound provided by the buzzer cannot differentiate the distance between obstacles. Therefore, this study proposes the existence of additional sound playback responses to differentiate far, middle, and near obstacles. Apart from that, the design of the prototype refers to the shape of a flashlight. The smart cane is designed using an Arduini UNO microcontroller with a rechargeable battery power supply with three response components, namely two ISD 1820 modules connected to a speaker to detect long distances (201-300 cm) with a